A Novel Method for Accurate Preoperative Templating for Total Hip Arthroplasty Using a Biplanar Digital Radiographic (EOS) System. Issue 4 (October 2020) - Huang, Jun; Zhu, Ye; Ma, Wenxia; Zhang, Zhigang; Shi, Weidong; Lin, Jun
Abstract : Background: Accurate preoperative planning for total hip arthroplasty (THA) relies on conventional anteroposterior radiographs. The difficulty of determining the magnification factor of radiographs is a major limitation. Despite the use of markers for calibration, identifying the plane of the hip joint is a major challenge. The aim of this study was to evaluate the accuracy of a novel method for image calibration and preoperative planning in THA involving the use of a biplanar radiographic (EOS imaging) system and a self-designed coin device. Methods: Biplanar radiographs (with the self-designed coin device) and a conventional anteroposterior radiograph (with a coin) were made for 26 patients after primary THA. The agreement between the actual and calculated diameters for each method was assessed using the concordance correlation coefficient (CCC) and Bland-Altman plots. In addition, 15 patients undergoing primary THA were prospectively enrolled to evaluate the EOS imaging-based method (EOS method), with biplanar radiographs made with use of the coin device. The accuracy of the preoperative predicted size of the implants was evaluated. Results: Both the EOS and conventional anteroposterior radiograph-based methods were reliable in repeated measurements of the diameter of the artificial femoral head in the reproducibility study, with the average CCCs for both methods >0.990. The agreement between the actual and EOS-based calculated diameters of the artificial femoral head was excellent, with a CCC of >0.990, while the agreement was poor between the actual and anteroposterior radiograph-based calculated diameters, with a CCC of <0.75. The EOS method exhibited a lower absolute difference (0.09 ± 0.07 mm) between the actual and calculated diameters compared with conventional anteroposterior radiography (1.26 ± 0.86 mm) (p < 0.001). EOS-based preoperative plans also exhibited excellent performance on the accuracy of the planning of the cups and stems; only 1 patient (6.7%) had a final implanted cup that differed by 1 size from the predicted size. Two patients (13.3%) had final implanted stems that differed by 1 size from the predicted size, and for 1 patient (6.7%), the stem size was off by ≥2 sizes. Conclusions: We describe a novel and easy-to-use method for the accurate calibration of radiographs and preoperative planning for THA. The EOS method evaluated in this study is an alternative method for preoperative planning in clinical practice.